2014
DOI: 10.1177/0956797614534450
|View full text |Cite
|
Sign up to set email alerts
|

The Moral Ties That Bind . . . Even to Out-Groups: The Interactive Effect of Moral Identity and the Binding Moral Foundations

Abstract: Throughout history, principles such as obedience, loyalty, and purity have been instrumental in binding people together and helping them thrive as groups, tribes, and nations. However, these same principles have also led to in-group favoritism, war, and even genocide. Does adhering to the binding moral foundations that underlie such principles unavoidably lead to the derogation of out-group members? We demonstrated that for people with a strong moral identity, the answer is "no," because they are more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 37 publications
5
94
0
2
Order By: Relevance
“…According to Kugler and his colleagues (2014), binding moral foundations are positively related to anti-immigrant attitudes, while the associations with individualizing foundations are negative. Low and Wui (2016) reported negative relationship between individualizing foundations and negative attitudes towards the poor, whereas Smith, Aquino, Koleva, and Graham (2014) found that binding moral foundations enhanced support for the torture of outgroup members among respondents with weak moral identity.…”
Section: Threat and Moral Foundationsmentioning
confidence: 96%
“…According to Kugler and his colleagues (2014), binding moral foundations are positively related to anti-immigrant attitudes, while the associations with individualizing foundations are negative. Low and Wui (2016) reported negative relationship between individualizing foundations and negative attitudes towards the poor, whereas Smith, Aquino, Koleva, and Graham (2014) found that binding moral foundations enhanced support for the torture of outgroup members among respondents with weak moral identity.…”
Section: Threat and Moral Foundationsmentioning
confidence: 96%
“…MFT argues that these foundations are “binding” in that they encourage prioritization of group cohesion over the interests of the individual in numerous ways (Graham & Haidt, ; Smith, Aquino, Koleva, & Graham, ). For example, groups should thrive when their members are loyal, trustworthy team players and deferential to the authority of group leaders.…”
Section: Moral Foundations Theorymentioning
confidence: 99%
“…Strongly fused individuals’ hostility towards outgroup members reflects strong attachment to the ingroup rather than conservatism (Fredman et al, ). In short, regardless of where they fall on the political spectrum, strongly fused individuals have all the markings of endorsers of the binding foundations (e.g., Smith et al, ). Because moral foundations research most frequently refers to binding morals in the context of political groups, we measured fusion with one’s country and political party.…”
Section: Moral Foundations Theorymentioning
confidence: 99%
“…Also, those with religious tendencies strongly adhere to maintaining collective communities, which would insulate and reinforce their shared moral beliefs. This prioritization of their ingroup and traditional values has led prior researchers to suggest there may be a dark side to holding binding moral virtues (Smith et al, 2014). For example, religious affiliates have been found to be more prejudiced and less concerned towards outsiders (Johnson et al, 2010), to the point of hostility (Ramsay et al, 2014) and violence (Ginges et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it is assumed religious affiliation promotes moral behavior (Graham & Haidt, 2010), this may be restricted to those who are of the same denomination. This has been described as the ''dark side'' of the binding foundation (Smith, Aquino, Koleva, & Graham, 2014, p.1555. As such, religious social affiliations may impact an individual's moral behavior differently towards people within their group compared to outsiders (Hall, Matz, & Wood, 2010).…”
Section: Introductionmentioning
confidence: 99%